Mechanistic interpretation of the sorption of terbuthylazine pesticide onto aged microplastics - Junck, Johannes; Diagboya, Paul N.; Peqini, Aleksander; Rohnke, Marcus; Düring, Rolf-Alexander; Justus Liebig University Giessen (My University, 2024)
Microplastics (MPs) pose a global concern due to their ubiquitous distribution. Once in the environment, they are subject to aging, which changes their chemical-physical properties and ability to interact with organic pollutants, such as pesticides. Therefore, this study investigated the interaction of the hydrophobic herbicide terbuthylazine (TBA), which is widely used in agriculture, with artificially aged polyethylene (PE) MP (PE-MP) to understand how aging affects its sorption. PE was aged by an accelerated weathering process including UV irradiation, hydrogen peroxide, and ultrasonic treatment, and aged particles were characterized in comparison to pristine particles. Sorption kinetics were performed for aged and pristine materials, while further sorption studies with aged PE-MP included determining environmental factors such as pH, temperature, and TBA concentration. Sorption of TBA was found to be significantly lower on aged PE-MP compared to pristine particles because aging led to the formation of oxygen-containing functional groups, resulting in a reduction in hydrophobicity and the formation of negatively charged sites on oxidized surfaces. For pristine PE-MP, sorption kinetics were best described by the pseudo-second-order model, while it was intra-particle diffusion for aged PE-MP as a result of crack and pore formation. Sorption followed a decreasing trend with increasing pH, while it became less favorable at higher temperatures. The isotherm data revealed a complex sorption process on altered, heterogeneous surfaces involving hydrophobic interactions, hydrogen bonding, and π-π interactions, and the process was best described by the Sips adsorption isotherm model. Desorption was found to be low, confirming a strong interaction. However, thermodynamic results imply that increased temperatures, such as those resulting from climate change, could promote the re-release of TBA from aged PE-MP into the environment. Time-of-flight secondary ion mass spectrometry (ToF-SIMS) confirmed TBA sorption onto PE.
Keywords: ddc:630